SPORTS TRAINING OF MIDDLE DISTANCE RUNNERS TAKING INTO ACCOUNT THE PECULIARITIES OF THE ENERGY SUPPLY OF THEIR MUSCLE ACTIVITY - Klimenko, S.S.; Kadutskaya, L.A.; Domracheva, E.Yu.; Nesterenko, G.L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the main pedagogical conditions necessary to improve the effectiveness of the competitive activity of middle-distance runners, taking into account the peculiarities of the energy supply of their muscular activity. Methods and structure of the study. A survey of coaches and qualified runners was conducted. In total, 19 coaches of the highest category and 19 runners with the sports qualification "Master of Sports of Russia" were interviewed. A correlation analysis was carried out to assess the degree of influence of the level of development of physical qualities on the effectiveness of the competitive activity of runners at medium distances. Results and conclusions. It was revealed that the efficiency of middle-distance runners training can be increased by rationalizing the training process methodology, taking into account their individual characteristics of energy supply for their muscular activity, while maintaining the proportions of loads for improving physical qualities. The main physical quality that has the greatest impact on the effectiveness of the competitive activity of middle-distance runners is speed endurance.